Jan Zamoyski`s housing district in Zamość – implementation of PR-5 programme and modernisation efforts - Dmitruk, Michał (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2017)
Among the many prefabricated housing blocks built in Poland over the years from the 70s to the 90s of the twentieth century, Jan Zamoyski`s Housing District in Zamość deserves a special attention. Created as an implementation of the governmental PR-5 project has unique urban – architectural values and avant-garde technical solutions, unprecedented in any of the previously built large panel settlements in Poland. Currently, community administration office makes every effort to modernize, revitalize and maintain the modern utility standards of the buildings.